Epidemiology in country practice - Pickles, William Norman (J. Wright, 1939)
Epidemiology in Country Practice presents the development of the catarrhal jaundice and myalgia. It discusses the epidemiological and clinical observations of country doctors. It addresses the conditions of life of a country doctor. Some of the topics covered in the book are the appeal to improved medical research; methods of communicating medical research; techniques in acquisition of clinical data; types of diseases of the people living in the country; description of influenza, measles, scarlet fever, whooping-cough, and mumps; and diagnosis and behavior of chicken-pox and shingles. The desc.